KARAKTERISTIK OTAK-OTAK TULANG IKAN TODAK (Tylosurus crocodilus) DENGAN PENERAPAN TEKNOLOGI MODERN - Irawan, Dedy; Jumsurizal, Jumsurizal; Putri, R. Marwita Sari (Marinade, 2021)
Fishbone otak-otak is one of the processing the results of fisheries diversification. Fishbone otak-otak have a weakness, the bones in this product cannot be consumed, besides that the bones can cause mouth irritation, this is the application of modern technology is involved in overcoming weaknesses in consumption fishbone otak-otak. One of the modern technology namely with presto technology. The purpose of this research find outphysical (Organoleptic, Rendemen) and chemical (Proximate, Calcium, Bone Hardness) on the characteristics of the fishbone otak-otak swordfish (Tylosurus crocodilus). Method This uses a completely randomized design (CRD), consisting of 3 treatments, namely during 1 hour (T1), 1.5 hours (T2), 2 hours (T3) and 3 replications at a temperature of 115-120 oC. Result the best organoleptic testing is 1.5 hours treatment gave an average appearance value (2.47%), Odor (2.60%), Taste (2.60%) and Texture (2.50%). The results of the yield analysis were 1 hour (60%) 1.5 hours (59%) 2 hours (58%). Proximate analysis results based on treatment best get scorerate-ratewater content (54.44%) ash content (19.21%) fat content (5.64%) protein content (9.70%) carbohydrate content (22.04%). The highest result of calcium analysis is 6594.11 mg/ 100 g. The results of the analysis of bone hardness were 1061.75 g.